Sintesis dan Karakterisasi Semikonduktor TiO2 Doping Magnesium dengan Metode Hidrotermal: Synthesis and Characterization of Magnesium Doped TiO2 Semiconductor by Hydrothermal Method - Tika Paramitha; Khoirunnisa Utami; Yuki Martha Anggraini; Tifa Paramitha (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2023)
Semiconductors are materials that range between insulators and conductors in terms of conductivity value. Titanium Dioxide (TiO2) is a semiconductor that is widely applied to various things. TiO2 has the benefits, such as being environmentally stable and inexpensive. TiO2 is photoactive in the range of ultraviolet radiation due to the band gap value of 3.2 eV. However, ultraviolet is only produced from 5% of sunlight. The research aimed to narrow the band gap energy so as to maximize light absorption. This is done by modification with the addition of Mg elements to TiO2 materials at different mass variations of Mg (1%, 1.5%, 2%) to the mass of TiO2 which is often referred to as doping. TiO2 was doped by Mg using a hydrothermal method for 24 hours with a temperature of 180áµ’C, followed by 2 hours of calcination at 400áµ’C. Then, TiO2 and Mg-doped TiO2 particles were characterized by SEM-EDX, FTIR, and UV-Vis. Based on the results of TiO2 and Mg-doped TiO2 particle characterization using SEM, both particles are spherical in shape. The success of Mg doping was identified from the data of EDX characterization, which revealed that the mass % of the Mg component increased with the greater Mg doping concentration on TiO2 particles. There was no structural change following Mg doping on TiO2 particles, as evidenced by the same peak based on the results of FTIR characterization of TiO2 and Mg-doped TiO2 particles. Moreover, a 2% Mg mass doping on pure TiO2 resulted in a decrease in band gap energy to 3.16 eV, in which the pure TiO2 was 3.39 eV. The mass doping of Mg on TiO2 required further optimization to obtain the maximum band gap energy reduction for photocatalytic applications.